Development of symmetrical solid oxide fuel cell and electrolysis cell - Chan, Priscilla Yu Ying (Nanyang Technological University, 2021)
This study investigates the electrochemical performance of using Strontium Ferromolybdate (Sr2Fe1.5Mo0.5O6−δ, SFMO) perovskites as symmetrical electrodes under Solid Oxide Electrolysis Cell (SOEC) modes for water, pure carbon dioxide and co-electrolysis operations. SFMO was prepared through solution combustion synthesis at a calcination temperature of 1200°C while the electrolyte material LSGM was fabricated using solid-state sintering at 1450°C. Electrochemical impedance spectroscopy and polarisation studies were used for the evaluation of cell performance. High electrochemical performance and stability have been observed for water electrolysis under various steam contents of hydrogen atmosphere. In which, 20% water concentration showed the best results of 0.951 A cm^-2 with 0.295 Ω cm^2 at 800°C and 1.4V. Under pure carbon dioxide electrolysis at 800°C and 1.4V, the current density and polarisation resistance were 0.435 A cm^-2 and 0.350 Ω cm^2 respectively. As for the co-electrolysis operations under different gas contents, 50% stream with 50% carbon dioxide presented more stable results with 0.556 A cm^-2 and 0.5166 Ω cm^2 at 800°C and 1.4V. An unusual polarisation curve was observed for co-electrolysis at low water concentrations (3%), which also displayed a cell degradation when a short-term stability test was conducted. In this case, microstructures and phase identification of the SFMO and LSGM have been analysed using FESEM and XRD techniques. Parasitic behaviour for co-electrolysis is determined to be due to site chemical reaction of SFMO with carbon dioxide. Further research in this area can be conducted to evaluate the performance of SFMO electrodes in syngas production.